Sociodemographic aspects, satisfaction, loyalty, and motivations in religious tourism - Carvache-Franco, Mauricio (2024)
This research concentrated on pilgrimages within the context of religious tourism. It sought to accomplish the following goals: establish the main motivational factors in religious tourism, identify the relationship between sociodemographic aspects and motivations, and determine the relationship between the sociodemographic aspects of pilgrims with their satisfaction and loyalty. The study was conducted during the Christ of Miracles Pilgrimage in Lima, Peru. The sample consisted of 384 tourists who were surveyed on-site. The statistical techniques used included factorial and multiple regression analysis. The findings uncovered five motivational dimensions: religious experience, belief experience, escape experience, tourist experience, and shopping. The sociodemographic variables were correlated with the motivation for the escape experience, thus younger attendees, with higher educational levels or who attended the event fewer times had higher levels of motivation for the Escape. Age was correlated with satisfaction, older attendees were more satisfied and the number of attendees at the event was correlated with loyalty. The results will offer management recommendations for organizers of religious events and add valuable insights to the academic literature.